Inherent Characteristic and Steady Response Analysis of Aviation Gear with Thin-spoke - Wang Dayong (Jixie chuandong)
The thin- spoke structure gear model is established by using 3D modeling software,and the finite element software is used for the pre- processing. The load history on single tooth is obtained according to the dynamics equation and load distribution,which is applied on the basis of meshing time. By this means,the force condition of gear under operation condition is simulated. The inherent characteristic of gear with thin-spoke is calculated,the graph of travelling waves is plotted. The steady responses and dynamic stress under operation condition and resonance speed is calculated through the method of modal superposition and the curve of dynamic stress is drawn. This method applies to analyze steady responses under different speed conditions of any kinds of gear. It provides reference for stress check and optimum structure.